2017
DOI: 10.1088/1361-665x/aa77b3
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological formulation for the shape/temperature memory effect in amorphous polymers with multi-stress components

Abstract: By means of combining the influence of temperature and strain rate, and based on the cooperative Eyring model, a phenomenological formulation for the shape memory effect and temperature memory effect of an amorphous shape memory polymer (SMP) is proposed. The internal stress and stored mechanical energy are correlated to shape/temperature memory behaviours below and above the glass transition temperature. The working mechanism and fundamentals for the chemo-responsive shape memory behaviour in SMPs are further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Heating at 80 • C for several minutes triggered obvious shape recovery, along with the process of which the stretchable electrode was capable of healing the conductive pathways, enabling the lamp to enlighten again. and stored mechanical energy were found to be correlated to the shape/temperature memory behavior below and above the transition temperature [14]. It is well known that the Tm-type shape memory polymers, exhibited the so called stress-memory effect [15,16].…”
Section: Raman Spectra Investigations On the Microstructure Evolutionmentioning
confidence: 93%
See 1 more Smart Citation
“…Heating at 80 • C for several minutes triggered obvious shape recovery, along with the process of which the stretchable electrode was capable of healing the conductive pathways, enabling the lamp to enlighten again. and stored mechanical energy were found to be correlated to the shape/temperature memory behavior below and above the transition temperature [14]. It is well known that the Tm-type shape memory polymers, exhibited the so called stress-memory effect [15,16].…”
Section: Raman Spectra Investigations On the Microstructure Evolutionmentioning
confidence: 93%
“…The spectra results indicated that the release of the strain energy magnified micro-structural variations in the shape memory-enhanced self-healing process. The internal stress and stored mechanical energy were found to be correlated to the shape/temperature memory behavior below and above the transition temperature [14]. It is well known that the T m -type shape memory polymers, exhibited the so called stress-memory effect [15,16].…”
Section: Raman Spectra Investigations On the Microstructure Evolutionmentioning
confidence: 95%
“…In comparison with other types of soft materials such as electroactive elastomers and hydrogels, SMPs have unique and desirable shape memory capabilities owing to the pre-stored mechanical energy during the pre-deformation stage [4,5]. In terms of thermodynamics, SMP macromolecules are normally composed of two or more segments, at least one of which is the hard segment and the others of which is soft one [6,7]. A cooperative relaxation could happen between the hard and soft segments at temperatures below and above the glass transition temperature [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of thermodynamics, SMP macromolecules are normally composed of two or more segments, at least one of which is the hard segment and the others of which is soft one [6,7]. A cooperative relaxation could happen between the hard and soft segments at temperatures below and above the glass transition temperature [6][7][8]. Therefore, shape memory behavior of amorphous SMPs has been theoretically explained based on the thermo-visco-elasticity effects, and the mobility changes in the macromolecules has been linked to the changes in the viscosity or relaxation time using rheological elements [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation